Pengaruh Asisten Virtual Berbasis Artificial Intelligence Terhadap Integritas Sertifikasi Kompetensi Pemrograman secara Online - Pujiono, Imam Prayogo; Rachmawanto, Eko Hari; Hana, Fida Maisa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The use of virtual assistants based on Artificial Intelligence (AI) has shown a significant impact in various sectors, especially education. The presence of AI-based virtual assistants capable of answering questions from various topics creates new opportunities and challenges, especially regarding exams and assessments. This research examines the impact of using AI-based virtual assistants, specifically ChatGPT (GPT-4), on the integrity of programming competency certification carried out online. Through field experiments, the author took three online programming competency certifications related to